2013
DOI: 10.1007/s00114-013-1016-7
|View full text |Cite
|
Sign up to set email alerts
|

Variable virulence among isolates of Ascosphaera apis: testing the parasite–pathogen hypothesis for the evolution of polyandry in social insects

Abstract: The queens of many eusocial insect species are polyandrous. The evolution of polyandry from ancestral monoandry is intriguing because polyandry undermines the kin-selected benefits of high intracolonial relatedness that are understood to have been central to the evolution of eusociality. An accumulating body of evidence suggests that polyandry evolved from monoandry in part because genetically diverse colonies better resist infection by pathogens. However, a core assumption of the "parasite-pathogen hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In social Hymenoptera, strong support for improved disease resistance from increased genetic diversity has been demonstrated in bumblebees [51][52][53] and honeybees 40,[42][43][44][54][55][56][57] , while similar experiments in ants have produced contrasting results. While several ant species show no relationship between genetic diversity and pathogen resistance [97][98][99] , there are some that do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In social Hymenoptera, strong support for improved disease resistance from increased genetic diversity has been demonstrated in bumblebees [51][52][53] and honeybees 40,[42][43][44][54][55][56][57] , while similar experiments in ants have produced contrasting results. While several ant species show no relationship between genetic diversity and pathogen resistance [97][98][99] , there are some that do.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main hypotheses suggests that the increased genetic diversity that results from the high number of reproductives in a colony can strengthen their resistance toward pathogens 3,39,46 . Empirical studies have shown improved pathogen resistance from polyandry in bumblebees [51][52][53] , honeybees 40,[42][43][44][54][55][56][57] , and ants 58 , as well as from polygyny in ants 59 . The beneficial effect of genetic diversity on social immunity has been widely examined in social Hymenoptera, but its evidence in termites, the other major group of social insects, is scarce.…”
mentioning
confidence: 99%
“…Models of superinfection also predict that, within a superinfective pathogen species, many strains will occur with a high diversity of virulence levels, as superinfective competition will also take place within a species (Nowak and May, 1994). Indeed, variability in virulence of A. apis is observed (Lee et al, 2013), as well as a variation in host susceptibility (Vojvodic et al, 2011b). In our study, we did not use a single isolate of A. apis, but mixtures of several isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A genetically diverse host population is less likely to provide a favorable environment for pathogens, significantly reducing the prevalence and incidence of diseases; similar to how highly diverse plants have lower infection rates than less diverse plant species [ 35 ]. Evidence has shown that polyandry allows species to better resist infection by pathogens [ 36 ].…”
Section: Nonreproductive Swarming Can Increase Genetic Diversitymentioning
confidence: 99%